Economic sanctions and human rights: Quantifying the legal proportionality principle - Jerg Gutmann; Matthias Neuenkirch; Florian Neumeier; Armin Steinbach (Universität Trier, Fachbereich IV – Volkswirtschaftslehre, 2018)
The proportionality principle, as the cardinal principle of international law, includes a necessity and a proportionality test, both of which rest on empirical premises. The necessity test involves an assessment of whether a legal sanction is well-suited to achieve its objective. The proportionality test questions the causal link between the sanction and the human rights situation in the country against which the sanction is aimed. This study analyzes the empirical basis of the proportionality principle by examining the consequences of economic sanctions for the target country's human rights situation. We use endogenous treatment-regression models to test the empirical basis of the proportionality principle by estimating the causal average treatment effect of US economic sanctions on different types of human rights within a uniform empirical framework. We find that economic sanctions do not pass the legal necessity test in cases where the purpose of the sanctions is to improve the human rights situation. On the contrary, we find that such sanctions actually lead to a deterioration of the human rights situation. Moreover, our finding that the sanctions have no effect on basic, economic, and emancipatory human rights calls into question the dominant view that economic sanctions are disproportionate. On a general note, our study underscores the empirical contingencies of a core legal principle under international and national law.
Keywords: 330